Pengaruh Lama Waktu Perendaman Telur dalam Larutan Hormon Tiroksin (T4) Terhadap Daya Tetas, Pertumbuhan dan Kelangsungan Hidup Larva Ikan Gurami (Osphronemus gouramy) - Sri - Marnani; taufik budhi pramono; merry ayu andani (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
The thyroxine hormone is a hormone that can reduce high mortality and increase fish growth. The aim of this study was to determine the effect of long immersion time in the thyroxine hormone solution and a good time to increase hatching rate, growth and survival rate of Gourami larvae. The method used was a laboratory experiment with a completely randomized design. Treatment of egg immersion time in thyroxine hormone solution with a dose of 0.1 mg / L, namely 0, 8, 16, 24 and 32 hours. Each treatment was carried out three replications. The results of the study indicated that the immersion time did not affect hatching rate, but it did affect the length growth and survival of gourami larvae (O. gouramy). The good immersion time is 16-24 hours with hatching rate values 97.67-99.00%, absolute length growth of 6.50-6.92 mm, relative length growth of 4.93-5.25%, and survival rate of 91.26-92.15%.